'Ego-dystonicity' in homosexuality: An Indian perspective. (June 2015) - Sebastian Maroky, Ami; Ratheesh, Aswin; Viswanath, Biju; Math, Suresh Bada; Chandrashekar, Channapatna R; Seshadri, Shekhar P
Background: Homosexual persons are targets of verbal and physical abuse, discrimination and face legal disadvantages in many countries, including India. These external factors could play a role in determining discomfort with their sexuality. Aims: We ascertained the association between ego-dystonicity of sexual orientation and indices of perceived acceptance, stigma and awareness of possible normative lifestyles. Methods: Fifty-one self-identified adult homosexual men were assessed using online questionnaires that covered information including their socio-demographic details; a Visual Analog Scale (VAS) that measured their degree of discomfort with their sexuality; Reactions to Homosexuality Scale, Perceived Acceptance Scale, Modified China Men Who Have Sex with Men (MSM) Stigma scale; and trait version of the Positive and Negative Affect Scale. The participants were also asked to provide a written narrative of their experiences which influenced their comfort with their sexuality. Results: Discomfort with sexuality significantly correlated with education, acceptance by friends and family, legal disadvantages, awareness and accessibility to non-heteronormative lifestyles and support systems and trait affect. Only acceptance by friends and awareness showed significance on linear regression. Qualitative analyses revealed external attributions for discomfort. Conclusions: Modifying external factors, reducing legal restrictions and improving societal acceptance and support systems could reduce 'ego-dystonicity'. 'Ego-dystonicity' as a determinant for psychiatric classification and intervention needs to be reexamined.